Management of Occurring Threats to Wooden Monasteries in Mandalay: A Case Study of Maha-Minhtin Monastery | မန္တလေးမြို့ရှိသစ်သားဘုန်းကြီးကျောင်းများ ကြုံတွေ့နေရသည့် ဘေးအန္တရာယ်များကိုစီမံခန့်ခွဲခြင်း- မဟာမင်းထင်ဘုန်းကြီးကျောင်း ကို လေ့လာခြင်း - Mary Oo; Thet Oo (SPAFA Journal, 2023)
Pyu ancient cities and Bagan are recognized as World Heritage Sites in Myanmar. Likewise, Mandalay is on one of the tentative lists under the name of Ancient Cities of Upper Myanmar: Innwa, Amarapura, Sagaing, Mingun, and Mandalay, submitted in 1996. As Mandalay is the cultural capital of Myanmar, many intangible and tangible cultural heritage from different times (the late Konbaung, the colonial era and the pre-independence era, etc.) remain. It is striving to become a world heritage site by means of these factors. Out of the tangible heritage structures, most are religious buildings (stupas, temples, monasteries, churches, mosques, Hindu temples, etc.). Almost all of these buildings are still in use by way of their original functions and are being maintained by the relevant authorities to the best of their ability. Additionally, these buildings were made of weather-resistant materials such as brick and stone, so they still exist intact to this day. However, amid all of them, the late Konbaung period wooden monasteries face grievingly confronting devastations. For the wooden monasteries are almost a hundred years old and have been impaired by many natural disasters. They have been encountering disturbing threats owing to the decay of wood, the scarcity of quality wood for replacement, and poor maintenance techniques. Systematic management for the long-term existence of the wooden monasteries of the late Konbaung era, in the Unesco World Heritage tentative site of Mandalay is important. Therefore, in this research paper, the case study of a monastery facing the worst possible situation is identified and described followed by a discussion on the ways to prevent these hazards and locally appropriate maintenance recommendations will be looked for and presented. A lot of research that is associated with the architecture of wooden monasteries in Mandalay, histories and the wood has been done by various local and foreign professionals. However, this research aims to fill this gap, as the reasons for the deterioration of these wooden monasteries, challenging threats, and experiencing facts to be long-lasting have not been systematically researched yet.